Socio-economic assessments of Hepatitis C Virus infection: Evidence from Vehari district of Pakistan - Dilshad Ahmed; Muhammad Shakeel; Bilal Tariq; Tariq Mahmood (Archives of Hepatitis Research - Peertechz Publications, 2021)
The present study corroborates the annual average economic burden of Hepatitis C virus (HCV) and socio-economic factors concerning awareness of HCV in Pakistan. The data of 100 patients collected via conducting interviews/questionnaire from different hospitals to gauge the direct/indirect pecuniary costs of HCV infection. Bottom up approach, Human capital approach and Tobit model were applied to compute the costs and determinants of HCV and its awareness. Results demonstrate that annual average economic burden was 1379.2734 USD. The knowledge/awareness status is vulnerable implying that most of the population has limited knowledge about HCV. Poverty and low levels of schooling years are amidst the main causes of low awareness vis-a-vis HCV and their cures, ceteris paribus. Income, education and test screening have positive impact on knowledge score of HCV. The findings imply for promotion of awareness campaigns and development of diagnostic centers to increase the knowledge score and early diagnostic of HCV.